Pemahaman Liberalisme dalam Perspektif Islam dan Kristen Studi terhadap Pandangan Majelis Ulama Indonesia (MUI) dan Persekutuan Injili Indonesia - Harahap, Danil Arif; Hidayat, Muhammad; Harahap, Hotmatua Paralihan (Asian Journal of Islamic Studies and Da'wah, 2023)
This study discusses the understanding of religious liberalism from an Islamic and Christian perspective. Liberal values are prohibited by the MUI, so Islam is contrary to the basic right to freedom. In rejecting the principle of freedom, the meaning is often misinterpreted as "free as freely as possible without limits" which is not actually the freedom of anarchy. Misunderstandings occur among orthodox Islamic circles, but also among secular nationalities. Liberalism is related to individualism on the one hand and imperialist capitalism on the other. Liberalism understands that it experiences development and change and can even form politics and political parties. The opposite of liberalism is fundamentalism, both in the economic and religious fields. What is meant by liberal freedom here is freedom that is institutionalized in constitutional law, freedom and human rights are the foundation of democracy, because with these principles every citizen is given the right to choose and be elected. Christian liberalism, they want to return to the holy book because Christianity has various kinds of sects and interpretations of the holy book at this time, so liberal Protestant Christians want to return to the new teachings, because it is opposed by fundamentalism, therefore again, sects and sects are born again. currents in Christianity. Liberalism in Islam is a renewal of good life, in the study of fiqh, kalam science, and Sufism. They want to make reforms with certain grounds and reasons. So the MUI forbids the flow of religious liberalism, whereas in Christianity the flow of religious liberalism is not prohibited because the Christian religion, every time they have an understanding of their own religion, they immediately create their own sects and sects, because the Christian religion has no valid guidelines, the Bible follows the times. which is very different from Islam, whatever actions and actions are based on the Koran and hadith. The method used is a qualitative method, which is based on the theory of liberalism.